Penegakan Hukum Terhadap Tindak Pidana Penggelapan dalam Jabatan (Studi Putusan Nomor: 593/Pid.B/2024/PN Tjk) - Purba, Ria Ermina; Marpaung, Lintje Anna; Ainita, Okta (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze law enforcement against the crime of embezzlement in office and the factors causing the crime. Based on the case study of Decision Number 593/Pid.B/2024/PN Tjk, this study focuses on examining and understanding law enforcement efforts and the factors causing the crime of embezzlement in office, which often involve internal and external factors that influence the behavior of the perpetrators. This study uses a problem-based approach in the form of a normative and empirical legal approach. Based on the study, it was concluded that law enforcement efforts against the crime of embezzlement in office were in accordance with the procedures of Article 374 of the Criminal Code, starting from the reporter's report, summons, arrest, to the submission of the case to the judge who sentenced him to five months in prison. The factors causing this crime are divided into internal factors, such as low integrity, economic motives, and lack of supervision, as well as external factors, such as a consumptive lifestyle and social pressure. The combination of these two factors often leads to embezzlement in office. To prevent similar crimes, it is important to strengthen individual integrity, increase supervision, and provide an understanding of professional ethics and legal impacts.